Growth and properties of epitaxial PtMn/NiFe bilayers on Si (001) substrate containing directly deposited ordered PtMn - Choi, Y; Petford-Long, A; Ward, R (2005)
Equiatomic PtMn layers have been grown epitaxially on Si (001), with the face-centered tetragonal L1 0-ordered antiferromagnetic phase forming without post-growth magnetic field annealing. The thickness dependence of the exchange anisotropy field and coercivity of the NiFe ferromagnetic layer in the epitaxial PtMn/NiFe exchange-coupled bilayers showed the critical thickness of the PtMn to be 10 nm. The exchange biasing properties are stabilised above a PtMn thickness of 15 nm which is much lower than that for polycrystalline PtMn-based exchange-biased systems. The highest value of exchange-bias is observed for a NiFe ferromagnetic layer thickness of 6 nm. The temperature dependence of the magnetic properties in the range 50-400 K shows that H ex and H c increase monotonically in a quasi-linear manner as temperature decreases. Non-saturation of the in-plane magnetisation component of the PtMn, due to the Néel axis lying normal to the interface, is suggested to be responsible for the temperature dependence. © 2005 Elsevier B.V. All rights reserved.